Genetic Counseling in a Couple with Primary Infertility - Peter Ivan Hadiprajitno; Sultana Faradz (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Couples unable to conceive and bear children could feel deep disappointment, often leading to depression. Infertility is one of the main reasons couples are not able to have children. Genetic counseling role in infertility ranges from explanation about possible genetic causes of infertility, pregnancy planning, and advice for treatment. Case Presentation: A couple with 16 years of infertility was referred to the genetic clinic at National Diponegoro Hospital. The 42 years old female had previous history of diabetes mellitus, obesity, and had treatment of epilepsy/seizure 15 years ago with routine carbamazepine therapy for 2 years, while her 42 years old husband had active hepatitis B infection for 15 years. This couple underwent insemination program twice and once completed In Vitro Fertilization (IVF), both management bearing no successful implantation or viable pregnancy. Recently, she underwent a laparoscopy procedure, which gave new diagnosis of endometriosis and adenomyosis. Chromosomal examination and Methylenetetrahydrofolate Reductase (MTHFR) C677T and A1298C alleles analysis were done in our laboratory. Both individuals carried normal karyotypes and MTHFR analysis was homozygote wild type allele. Currently, this couple has accepted their conditions. They still want to bear a child although she is at a crucial ageConclusion: Infertility is a challenging and comprehensive problem. As healthcare professionals, we encounter problems not only in diagnosis and management, but also psychological and emotional dilemma. Genetic counseling is needed to solve the problems and avoid patient’s psychological distress.